Upaya Meningkatkan Brand UMKM Binaan Baitul Maal Hidayatullah Depok melalui Pelatihan Pengelolaan Media Sosial - Hanathasia, Mirana; Prastari, Aprilina; Fortunisa, Ananda; Savitri Jatayusati, Haura (LPkM Universitas Bakrie, 2024)
In the middle of the widespread use of social media by Small and Medium Enterprises (SMEs) for promoting their business, some assisted SMEs have yet to maximize the use of this medium fully. Among them are assisted SMEs under Baitul Maal Hidayatullah's (BMH) supervision. Recognizing this condition, Lecturers from the Communication and Management programs of Bakrie University, through the CSR Komunikasih program, initiated the PkM “Improving Assisted UMKM of Baitul Maal Hidayatullah (BMH) Depok through Social Media Management Workshop”. This program aims to prepare assisted SMEs’ knowledge and skills to manage social media in developing brands. The program utilizes both online and offline workshops, as well as mentoring for assisted SMEs. It includes two online workshops, one offline workshop, and a month of post-workshop mentoring for SMEs. The event was attended by eight assisted SMEs of BMH, as well as six students under BMH’s supervision. The program results indicate that over 90% of participants gained an understanding of social media content production for branding and promoting their products. However, some challenges were identified, including limited time for assisted SMEs, technological gaps among assisted SMEs, and time and tool constraints for BMH-supervised students in creating content and following the supervisor's guidance.